The Power of the Government: China's Family Planning Leading. Group and the Fertility Decline since 1970 - Yi Chen; Yingfei Huang (Global Labor Organization (GLO), 2018)
China introduced its world-famous One-Child Policy in 1979. However, its fertility appears to have declined even faster in the early 1970s than it did after 1979. In this study, we highlight the importance of the Family Planning Leading Group in understanding the fertility decline since the early 1970s. In 1970, provinces gradually established an institution named the Family Planning Leading Group to facilitate the restoration of family planning, which had previously been interrupted by the outbreak of the Cultural Revolution. An important feature of this policy change is that the process differed by province. We find provinces that formed the leading group earlier also experienced an earlier decline in the fertility rate. Exploiting this provincial variation in establishment year, we estimate a difference-in-difference model that can explain about half of the decline in China's total fertility rate from 5.7 in 1969 to 2.7 in 1978. In comparison to the 1979 One-Child Policy, which previous research has widely treated as an exogenous shock to the fertility rate, our empirical strategy has three features: it captures a greater decline in the fertility rate, does not result in a contemporaneous increase in the sex ratio, and is robust to the inclusion of province-specific trends.
Keywords: J13; 330; Family Planning; Fertility Rate; Sex Ratio